Optimasi Suhu terhadap Pertumbuhan dan Kelulushidupan Ikan Heckel Discus (Symphysodon discus) - Triajiatma, Fiko; Julyantoro, Pande Gde Sasmita; Waskitasari, Alfi Hermawati (Current Trends in Aquatic Science, 2023)
This study aims to determine the optimization of temperature on the growth and survival of discus fish. The treatments used were different temperatures at 25°C, 28°C, and 31°C. Discus fish maintenance is carried out in 3 aquariums with a size of 120 × 40 × 40 cm which have been given a filter, aeration and heater. The water used is 120 liters, which has been aerated for 24 hours with a predetermined temperature using a heater (50W) and a water change of about 25% every week. Feeding is done by the satiation method, given 3 times a day with frozen worms where after 1 hour of feeding will be done to clean the remaining feed. Sampling of water quality (pH) using manual sampling method as a supporting parameter. The test fish used in this study were 5 cm discus fish. The number of fish used was 27 fish, and measurements were taken every 15 days with 3 repetitions. Length and weight growth of discus fish increased during the study. The growth of discus fish ( Symphysodon sp.) treated at 31°C was the most optimum growth with absolute length reaching 1,56 cm and absolute weight of 3,55 g compared to the 25°C and 28°C temperature treatments. The survival rate of discus fish in the 25° C, 28° C, and 31° C temperature treatments has a survival rate value of 100% and water quality that remains stable due to optimum temperature vulnerability.